PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN PENDEKATAN KONTEKSTUAL SISWA KELAS VIII MTs DARUL AMIN - Ernandi, Juliansyah; Syambasril, Syambasril; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is based on the weakness of MTs student skill. Darul Amin Pontianak in writing poetry. The type of research used is classroom action research (PTK). Qualitative research forms and descriptive methods. The data sources of this research are teachers and students of class VIII of 31 students. Data in this research is planning, implementation, and result of writing poetry. The technique in this research is the technique of test and technique of nontes. Results obtained from the study average student learning outcomes on pretest with an average of 64.37. Results of writing students in the first cycle using the contextual approach has increased by an average of 75.48. The value in cycle II with an average of 79.35. Based on the data of student writing, from cycle I cycle II also increased. The use of contextual approach in the process of writing poetry learning can foster motivation and enthusiasm of students in learning. Students are required to actively seek and find their learning in a way, kontruktivisme, inquiry, ask community, modeling, reflection, and real assessment.Keywords: poetry writing skill, contextual approach.